2011
DOI: 10.1111/j.1472-765x.2011.03150.x
|View full text |Cite
|
Sign up to set email alerts
|

Freezing and freeze-drying of the bacterium Rahnella aquatilis BNM 0523: study of protecting agents, rehydration media and freezing temperatures

Abstract: Aims:  The aim of the present study was to evaluate and compare freezing and freeze‐drying treatments for conserving Rahnella aquatilis (BNM 0523) with the goal to achieve an adequate commercial formulation of this biocontrol agent. Methods and Results:  The effect of several protective agents, rehydration media and freezing temperatures on the viability and functional activity of the R. aquatilis was investigated. The storage stability at 3 months and 4 years was determined by checking the viability of the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 15 publications
1
19
0
1
Order By: Relevance
“…In contrast, CPA-8 cells amended with sucrose or sucrose plus SM provided higher degree of cell protection during drying. Other authors have reported the beneficial role of sugars (Costa et al, 2000;Navarta et al, 2011;Zhan et al, 2011), which replace structural water in membrane after rehydration and prevent unfolding and aggregation of proteins (Champagne et al, 1991). The results obtained when MgSO4 was added to CPA-8 cells prior FD -alone or in mixture with SM-are in agreement with the work conducted by Yánez-Mendizábal et al (2012b).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In contrast, CPA-8 cells amended with sucrose or sucrose plus SM provided higher degree of cell protection during drying. Other authors have reported the beneficial role of sugars (Costa et al, 2000;Navarta et al, 2011;Zhan et al, 2011), which replace structural water in membrane after rehydration and prevent unfolding and aggregation of proteins (Champagne et al, 1991). The results obtained when MgSO4 was added to CPA-8 cells prior FD -alone or in mixture with SM-are in agreement with the work conducted by Yánez-Mendizábal et al (2012b).…”
Section: Discussionsupporting
confidence: 82%
“…The SM at concentrations of 1-10 % has often been used for cryopreservation but even more frequently in mixtures with other cryoprotectants (Hubalek, 2003;Li & Tian, 2007). As described Navarta et al (2011), the use of SM in the FD process of the BCA Ranhella aquatilis had lower protective effect than the SM used in combination with other additives such as sugars or polyols.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A potential alternative is to freeze pathogen-free faeces with a cryoprotectant in order to suspend microbial activity without damage to the cells. The use of non-toxic cryoprotectant agents is a common practice, with chemicals such as glycerol, skim milk, and sugar compounds frequently cited either as stand-alone reagents [Dan et al, 1989;Bonten et al, 1997;Cody et al, 2008;Savini et al, 2010;Kanmani et al, 2011] or in combination [O'Brien et al, 2001;Kanmani et al, 2011;Navarta et al, 2011]. The relative efficacies of these reagents is highly variable, although as stand-alone reagents glycerol and skim milk additives are consistently more effective than either sugar or other commercial additives [Bonten et al, 1997;Kanmani et al, 2011;Navarta et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…The use of non-toxic cryoprotectant agents is a common practice, with chemicals such as glycerol, skim milk, and sugar compounds frequently cited either as stand-alone reagents [Dan et al, 1989;Bonten et al, 1997;Cody et al, 2008;Savini et al, 2010;Kanmani et al, 2011] or in combination [O'Brien et al, 2001;Kanmani et al, 2011;Navarta et al, 2011]. The relative efficacies of these reagents is highly variable, although as stand-alone reagents glycerol and skim milk additives are consistently more effective than either sugar or other commercial additives [Bonten et al, 1997;Kanmani et al, 2011;Navarta et al, 2011]. Between skim milk and glycerol additives, there are varying reports of comparative efficacy, although these are often confounded by additional factors such as the bacterial strains tested, quantities used and freezing regime [Cody et al, 2008;Savini et al, 2010;Kanmani et al, 2011;Navarta et al, 2011].…”
Section: Introductionmentioning
confidence: 99%